Implementasi Problem Based Learning dalam Meningkatkan Hasil Belajar PAI Siswa Kelas IX.A di SMP Dewantara Kabupaten Bekasi - Asa Nadira Pramesti; Auliya Hasanah; Syifa Luthfiani; Nur Aini Farida (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
At several levels of education, particularly at SMP Dewantara in Bekasi Regency, students continue to face difficulties in achieving satisfactory learning outcomes in the Islamic Religious Education (PAI) subject. The predominantly lecture-based teaching style in class IX.A has not been effective in encouraging active student participation, resulting in low mastery of the subject matter. The aim of this study is to improve learning outcomes by integrating the Problem-Based Learning (PBL) model into PAI instruction. This study involved 12 students from class IX.A as subjects and was conducted over two cycles using a collaborative Classroom Action Research (CAR) strategy. Data were analyzed both qualitatively and quantitatively through observations, tests, and interviews. Based on the collected data, students' average scores increased significantly from 76.67 before the intervention to 98.33 in the second cycle. Learning mastery also improved from 58% to 100%. By creating a more dynamic, collaborative, and real-world-relevant learning environment, the PBL approach proved effective in helping students gain a deeper understanding of the subject matter.